IMPLEMENTATION OF THE POLLUTER PAYS PRINCIPLE AS THE BASIS FOR CORPORATE CRIMINAL LIABILITY IN FOREST ENCROACHMENT CRIMES - Rocmad Dwi Riwayanto; Muklis Al'anam (Universitas Bengkulu, 2026)
Deforestation by corporations is a serious environmental crime and has a significant impact on ecosystem damage and sustainable development. The objectives of this study are to: (1) analyze the application of the Polluter Pays Principle in corporate criminal liability for forest encroachment, and (2) identify normative and implementation weaknesses in enforcing this principle in Indonesia. The research method used is normative legal research with a legislative and conceptual approach, supported by an analysis of law enforcement practices. The results of the study indicate that the implementation of PPPs in cases of forest encroachment is still limited to administrative and civil sanctions, while its utilization in the criminal justice system is not optimal. Three main problems found are: (1) the absence of a standard for assessing ecological losses that can be used to impose fines; (2) weak evidence of corporate interaction due to the complexity of organizational structures and the use of corporations; and (3) the lack of synchronization between the regulations of the Environmental Law and the Forestry Law in determining the form of criminal liability. The uniqueness of this study lies in the integration of the Polluter Pays Principle into a framework of corporate criminal liability based on a multi-doctrine approach (identification theory, indirect liability, and corporate culture theory) as a model for more effective law enforcement. Therefore, it is necessary to reformulate environmental criminal policy to emphasize the optimization of fines, ecological restoration, and systematic enforcement of corporate responsibility, so that the PPP principle can be implemented effectively and provide a deterrent effect. Keywords: Corporate Criminal Liability, Forest Encroachment, Polluter Pays Principle